Numerical Simulation of Magnetohydrodynamic Nanofluids Under the Influence of Shape Factor and Thermal Transport in a Porous Media Using CVFEM - Shah, Zahir; Babazadeh, Houman; Kumam, Poom; Shafee, Ahmad; Thounthong, Phatiphat (Frontiers in Physics, 2019)
In this article, the migration of nanomaterials through a permeable domain was modeled numerically. Aluminum oxide was dispersed into testing fluid which was selected water in the current paper. Utilizing Darcy LAW for a porous medium helps us to find simpler form of equations. Influences of shape factor and radiation on the thermal conduct of nanoparticles within a porous region were scrutinized. Nanomaterial within such region is applied under the Lorentz force. CVFEM approach for simulation goals has been applied. This approach provides the advantages of two common CFD methods. Impacts of radiation, magnetic, buoyancy parameters on the treatment of nanomaterials were demonstrated. Outcomes showed that greater amounts of shape factor cause stronger convection. Reverse relationships exist between the Hartmann number and temperature gradient.